Effect of Steel Bead Wires Extracted from Recycled Tires on the Mechanical Properties of Concrete - Mohammed Ali, Salim; Ali Abdalla Elsageer, Mohammed (International Journal of Engineering Research, 2023)
Concrete plays an important role as a construction material in the worldwide for compressive strength. But the use of concrete as a structural material is limited to a certain extent by deficiencies like brittleness, poor tensile strength and poor resistance to impact strength, fatigue, low ductility, and low durability. Recently, worldwide researches have been devoted to the use of steel fibers recovered from consumed tires in concrete. For this goal, a bead wire having a diameter of 0.8 mm from recycled tires was extracted by a tire wire bead removal machine. A mix with a cement content of 420kg/m3 was produced with incorporating two different volumes of fiber 0.5%, and 1% of concrete volume, respectively, in addition to the reference samples (control) without steel fiber. Three different lengths 30-40-60 mm with the aspect ratio 37.5-50-75 respectively were used. Two maximum sizes of coarse aggregate were selected for the research. The maximum coarse aggregate sizes were 10 mm and 20 mm. A total of 36 cubes with 100 x 100 x 100 mm, 18 prisms with 150 mm x 150 mm x 750 mm, 36 cylinders with 150 mm diameter and 300 mm height were carryout and prepared in order to study the effect of the steel fibers (bead wires) on the mechanical properties of concrete. One mix was made without steel fibers (bead wire) extracted from recycled tires to be controlled. Samples of concrete incorporated with RTSF were tested compressive strength for cubic samples, indirect tensile strength test (Brazilian split test) for cylindrical samples, and flexural test for prismatic samples.